RBC transfusion is associated with increased risk of respiratory failure after pneumonectomy. Issue 4 (23rd March 2017) - Kidane, Biniam; Plourde, Madelaine; Leydier, Larissa; Chadi, Sami A.; Eckert, Kathleen; Srinathan, Sadeesh; Fortin, Dalilah; Frechette, Eric; Inculet, Richard I.; Malthaner, Richard A.
Abstract : Background and Objectives: Pneumonectomy is associated with high risk of respiratory complications. Our objective was to determine if transfusions are associated with increased rate of ARDS and respiratory failure in adults undergoing elective pneumonectomy. Methods: Retrospective cohort study of consecutive pneumonectomies undertaken at a tertiary hospital (2003‐2013). Multivariable logistic regression was performed to adjust for confounding factors. Results: ARDS and respiratory failure occurred in 12.4% ( n  = 20) and 19.2% ( n  = 31) of 161 pneumonectomy patients, respectively, and were more likely to occur in transfused patients ( P  = 0.03, P  < 0.001). pRBCs, FFP and platelets were transfused in 27% ( n  = 43), 6% ( n  = 9), and 2% ( n  = 3), respectively. On multivariable analyses utilizing blood products as continuous and binary variables, pRBC use was the only independent predictor of ARDS with odds ratio (OR) = 1.23 (95%CI:1.08‐1.39, P   =  0.002) and OR = 2.45 (95%CI:1.10‐5.49, P =  0.03), respectively. On multivariable analyses utilizing blood products as continuous and binary variables, pRBCs were the only independent predictor of respiratory failure with OR = 1.37 (95%CI:1.16‐1.60, P  < 0.001) and OR = 3.17 (95%CI:1.25‐8.02, P   =  0.02), respectively. Conclusions: Peri‐operative pRBC use appears to be an independent risk factor for ARDS and respiratory failure after pneumonectomy. There is a significant dose‐response relationship. Platelets and FFP did not appear to increase ARDS risk but this may be due to low utilization.